2016
DOI: 10.1039/c5sm01881a
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically triggered rupture of polymersomes

Abstract: Polymersomes are robust vesicles made from amphiphilic block co-polymers. Large populations of uniform giant polymersomes with defined, entrapped species can be made by templating of double-emulsions using microfluidics. In the present study, a series of two enzymatic reactions, one inside and the other outside of a polymersome, were designed to give rise to induced rupture of polymersomes. We measured how the kinetics of rupture were affected by altering enzyme concentration. These results suggest that protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Previously, Weitz and co‐workers reported that interaction between hydrophobic motif in the proteins and the hydrophobic membrane core of polymersome results in the adsorption of protein onto the polymersome membrane . Similarly, we observed that catalase encapsulated in the polymersome was adsorbed onto the inner leaflets of polymersome membrane . We assumed that if catalase can be associated with the outer leaflets of polymersome membrane, can enhance the motility of the polymersome.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Previously, Weitz and co‐workers reported that interaction between hydrophobic motif in the proteins and the hydrophobic membrane core of polymersome results in the adsorption of protein onto the polymersome membrane . Similarly, we observed that catalase encapsulated in the polymersome was adsorbed onto the inner leaflets of polymersome membrane . We assumed that if catalase can be associated with the outer leaflets of polymersome membrane, can enhance the motility of the polymersome.…”
Section: Resultssupporting
confidence: 63%
“…Polymersomes are formed by hydrating a thin film of OB(10–25) in an aqueous solution containing catalase. Catalase was chosen as the model enzyme because its substrate, H 2 O 2 is small and relatively neutral and passes freely through the membrane of polymersomes . We estimate that after assembly, the polymersomes encapsulate ≈0.6 × 10 −6 m catalase within the lumen (see the Experimental Section).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dispersed communities of synthetic protocells based on mixed populations of lipid vesicles, [1,2] polymersomes, [3,4] colloidosomes, [5] proteinosomes, [6] and coacervate microdroplets [7][8][9] provide an attractive opportunity to develop functionally interactive microcompartmentalized systems capable of chemical communication, [10][11][12][13][14][15][16][17] sensing, [18] signal-induced differentiation, [19,20] distributed computing, [21] oligonucleotide trafficking, [22] and enzyme-powered buoyancy. [23] Increasing the complexity of these consortia by exploiting matter and energy fluxes to drive cognate interactions remains ak ey challenge and ac ritical step towards synthetic protocell ecosystems exhibiting higher order contact-dependent behavior, such as artificial phagocytosis [24,25] and prototissue assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, enzyme‐driven rupture of polymersome membranes have recently been explored by the Hammer group . In their work, catalase is encapsulated in giant PEG‐ b ‐PBD vesicles, and glucose oxidase is introduced to the outer solution.…”
Section: Introductionmentioning
confidence: 99%